The effect of the chemical character of ionic liquids on biomass pre-treatment and posterior enzymatic hydrolysis - Bernardo, Joana (2020)
ABSTRACT: Ionic liquids have been recognised as interesting solvents applicable in efficient lignocellulosic biomass valorisation, especially in biomass fractionation into individual polymeric components or direct hydrolysis of some biomass fractions. Considering the chemical character of ionic liquids, two different approaches paved the way for the fractionation of biomass. The first strategy integrated a pre-treatment, hydrolysis and conversion of biomass through the employment of hydrogen-bond acidic 1-ethyl-3-methyimidazolim hydrogen sulphate ionic liquid. The second strategy relied on the use of a three-step fractionation process with hydrogen-bond basic 1-ethyl-3-methylimidazolium acetate to produce high purity cellulose, hemicellulose and lignin fractions. The proposed approaches were scrutinised for wheat straw and eucalyptus residues. These different biomasses enabled an understanding that enzymatic hydrolysis yields are dependent on the crystallinity of the pre-treated biomass. The use of acetate based ionic liquid allowed crystalline cellulose I to change to cellulose II and consequently enhanced the glucan to glucose yield to 93.1 +/- 4.1 mol% and 82.9 +/- 1.2 mol% for wheat straw and eucalyptus, respectively. However, for hydrogen sulphate ionic liquid, the same enzymatic hydrolysis yields were 61.6 +/- 0.2 mol% for wheat straw and only 7.9 +/- 0.3 mol% for eucalyptus residues. These results demonstrate the importance of both ionic liquid character and biomass type for efficient biomass processing.